2022
DOI: 10.1039/d2fo01739c
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β-but not Tau-induced neurotoxicity is suppressed by Manuka honeyviaHSP-16.2 and SKN-1/Nrf2 pathways in anin vivomodel of Alzheimer's disease

Abstract: Alzheimer's is a chronic degenerative disease of the central nervous system considered the first cause of dementia in the world. It is characterized by two etiopathological events related to oxidative...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 79 publications
(155 reference statements)
0
4
0
Order By: Relevance
“…In this way, some extracts obtained from the food industry have proven their efficacy in this worm model. Extracts derived from honey displayed the potential to enhance mobility parameters in BR5706 worms [ 50 , 51 ]. For example, an avocado honey extract increased stretching efforts, swimming speed, and overall activity in BR5706-treated worms compared to untreated ones [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, some extracts obtained from the food industry have proven their efficacy in this worm model. Extracts derived from honey displayed the potential to enhance mobility parameters in BR5706 worms [ 50 , 51 ]. For example, an avocado honey extract increased stretching efforts, swimming speed, and overall activity in BR5706-treated worms compared to untreated ones [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…3.6.6. Acute Lethal Toxicity Assay Acute toxicity assay was carried out using the wild-type N2 synchronized L4 following the methodology proposed by Navarro-Hortal and collaborators [50]. The results obtained from this assay were employed to select the concentration for the assays.…”
Section: Mitochondrial Ros Content Determinationmentioning
confidence: 99%
“…The total flavonoid content (TFC) was determined according to the aluminum chloride colorimetric method with some modifications [ 15 ]. Briefly, OL extracts and standards (catechin) were mixed with sodium nitrite for 6 min in a 96-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…Certain by-products, including olive leaves, have also shown promise in combating AD [29]. Moreover, the potential therapeutic effects of honey in the context of AD have been explored (e.g., [30,31]). Additionally, over the several last years, an increasing number of studies in animal models have indicated the capability of different plant extracts used in traditional Chinese medicine to treat AD [32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%